Modelo in vitro de barreira epitelial tubular na nefropatia diabética : efeito do tratamento com altas concentrações de glicose e ácidos graxos em células MDCK = In vitro model of renal tubular epithelial barrier in the context of the diabetic nephropathy: effect of treatment with high glucose and fatty acids in MDCK cells - Canuto, Leandro Pereira, 1994- (2018)
Orientador: Carla Beatriz Collares Buzato